2022
DOI: 10.1111/jonm.13642
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' ratings of compassionate nursing leadership during the Covid‐19 pandemic—A descriptive cross‐sectional study

Abstract: Aim The aim of this study is to investigate how intensive and emergency nurses rated the adequacy of compassionate leadership during the early stages of the Covid‐19 pandemic. Background The pandemic has resulted in nurses' increased stress and need for compassion from leaders. Compassionate leadership is here defined as a number of leadership practices based on altruistic values and emotional intelligence. Method This is a quantitative descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
0
18
0
3
Order By: Relevance
“…Organizational investment in leadership could also support this, as it has been identified that having supportive and credible leaders results in nurses feeling valued (Cope et al, 2016). Compassion leadership, a growing topic in the literature, is based on values to support others' wellbeing and emotional intelligence while focusing on a person's strengths (Salminen‐Tuomaala & Seppälä, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Organizational investment in leadership could also support this, as it has been identified that having supportive and credible leaders results in nurses feeling valued (Cope et al, 2016). Compassion leadership, a growing topic in the literature, is based on values to support others' wellbeing and emotional intelligence while focusing on a person's strengths (Salminen‐Tuomaala & Seppälä, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Research confirms that empowering leadership practices, for example, transformational leadership, can influence nurse retention and work engagement. [6,41,42] Some researchers, for example Schuck [43] and de Zulueta, [44] have strongly advocated compassionate leadership, which emphasizes presence and empathy and goes beyond traditional leader-follower roles by seeing leadership as a dynamic shared or distributed process. Last, according to some participants in this study, nurses should consider the impact their negative attitudes have on the image and appreciation of the nursing profession.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Nursing has become less appealing due to excessive workloads, prolonged shifts, and stress. [3][4][5][6] A study in Finland revealed that work demands are frequently experienced as overwhelming and the working conditions as poor. [7] According to the Finnish Institute of Occupational Health, the attractiveness of nursing and nurses' well-being at work is impaired by constant changes, insecurity, and lack of influence.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative data was converted into qualitative data following the JBI convergent integrated approach for MMSR by extracting the quantitative data and translating it into textual data based on the research questions by repeated detailed examination (Lizarondo et al , 2020). Data was collected from two of the quantitative studies (Salminen-Tuomaala and Seppälä, 2022a; Sansó et al , 2022), and three quantitative studies (López-Díaz et al , 2022; Papadopoulos et al , 2021; Papadopoulos et al , 2022) had already reported their findings in a qualitative form. The qualitative data were then pooled with the data from the qualitative studies, allowing quantitative and qualitative data to be combined (Stern et al , 2021) (Supplementary Table 6).…”
Section: Methodsmentioning
confidence: 99%
“…Tuomaala and Seppälä, 2022a;Salminen-Tuomaala and Seppälä, 2022b;Sans o et al, 2022) and having emotional intelligence…”
unclassified